Empowerment of The Boni Hat Home Industry in Sidoarjo Through Productivity Optimization and Financial-Marketing Management Based on Green Economy Principles - Hidayatullah, Rachmad Syarifudin; Cahya, Septyan Budy; Alamsyah, Sayyidul Aulia; Ajiban, Mochammad Hildad (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aims to strengthen the business capacity of a home-based industry producing school apparel and accessories by enhancing its production processes, financial management, and digital marketing skills. Implemented over an eight-month period, the program included a needs assessment, training, technology adoption, and mentoring activities. The training covered operation and maintenance of an automatic pneumatic hat molding machine, structured financial recording using accounting software, and digital branding through social media platforms. The program partner, U.D. International, is a home-based MSME in Sidoarjo that produces school uniforms and related accessories. Evaluation employed a pretest–posttest questionnaire using a 4-point Likert scale to assess changes in participants’ knowledge, skills, and attitudes across production, finance, and marketing. Comparative descriptive analysis measured performance improvements, while direct observation validated production gains through reduced cycle time and increased daily output. The pneumatic machine reduced production time from 60–80 seconds per unit to approximately 15 seconds, increasing daily production capacity by about 50% and improving product quality consistency. Financial management practices shifted from unrecorded and mixed personal–business transactions to a structured system with clear cash flow and profit–loss reporting. In marketing, the program facilitated brand identity creation, online presence, and social media content strategies, which significantly increased audience engagement and market reach. The results indicate that integrated interventions in technology, management, and branding can substantially enhance productivity, professionalism, and market competitiveness among MSMEs. This community empowerment model is expected to be replicable for similar small-scale industries pursuing sustainable growth.